Effects of a Residential Multimodal Psychological Treatment in an Addicted Population, at 6 and 12 Months: Differences Between Men and Women - Santos-de-Pascual, Asunción; López-Cano, Luis Miguel; Alcántara-López, Mavi; Martínez-Pérez, Antonia; Castro-Sáez, Maravillas; Fernández-Fernández, Visitación; López-Soler, Concepción (Frontiers in Psychiatry, 2022)
The aim of this study is to explore the effects of a residential multimodal treatment intervention for an addict population. We gathered participants from the “Programa Base” (n = 166) of the Solidarity and Reinsertion Foundation of Murcia, and assessed the various problematic areas with the EuropASI at baseline level, 6 months and 12 months of treatment. We found improved outcomes in every area except for Legal Status. In addition, we found differences between male and female participants in their baseline evaluation, as well as between completers and non-completers. In conclusion, this data shows us some changes which occurred in individuals with problematic drug use during treatment, going further into the complex social reality which causes great suffering and damage to people and their families.